Analysis of Grade X Students' Conceptual Understanding in Solving Problems on Exponential and Logarithmic Competency Tests Based on Apos Theory - Ramadhan, Nur Ihsan; Chairuddin, Chairuddin; Tahir, Tahir (Universitas Sembilanbelas November Kolaka, 2025)
This study aims to determine the level of students' understanding of mathematical concepts in exponents and logarithms based on APOS theory at SMA Negeri 4 Binongko. This study uses a qualitative approach with a descriptive method. The research subjects consisted of three tenth-grade students selected based on high, medium, and low ability levels. Data were obtained through competency tests and in-depth interviews, then analyzed based on the four stages of the APOS theory, namely action, process, object, and schema. The results showed that students with high ability had reached the schema stage, students with medium ability were at the object stage, and students with low ability were at the process stage. This indicates that there are differences in the level of conceptual understanding among students according to their respective abilities. Thus, the application of the APOS theory proved to be effective in identifying and mapping students' mathematical understanding of exponents and logarithms. These findings indicate that the APOS theory can be used as a basis for designing learning that encourages the development of students' conceptual understanding in mathematics.